Physiological and electroencephalogram responses in goats subjected to pre-and during slaughter stress - Raghazli, Razlina; Othman, Azalea Hani; Kaka, Ubedullah; Abubakar, Ahmed A.; Imlan, Jurhamid Columbres; Hamzah, Hazilawati; Sazili, Awis Qurni; Goh, Yong Meng (Elsevier BV, 2021)
A comprehensive stress assessment is vital in understanding the impact of the pre-slaughter procedure on animal welfare. The transportation and handling process was commonly reported to cause stress in animals. This research utilises electroencephalography (EEG) as an alternative stress indicator to non-painful acute stress measurement. EEG has been proved to be instantaneous and sensitive with specific results. Therefore, this study was aimed to determine the stress level of goats subjected to two different transportation duration and the effect of lairage based on their EEG activities and blood parameters changes. Eighteen adult male goats were divided into two transportation stress groups based on the transport duration: the two-hour (TS2) and six-hour (TS6) groups. Then, each group was then again divided into three smaller groups according to the lairage duration, which was three-hour (L3), six-hour (L6), and overnight (L12) groups. Blood was sampled before transport, after transport, and during slaughter while EEG was recorded before transport, after transport, after lairage, and during slaughter. Results revealed that there was a significant decrease in beta wave activity compared to baseline in TS2 goats (P < 0.05) after transportation, whereas no significant difference was detected in the TS6 goats. At the same time, goats from the TS2 group showed increase in creatine kinase (CK) and lactate dehydrogenase (LDH) compared to that in TS6 goats. Together with the observed cortisol concentration, these findings showed that the TS6 goats were fully adapted to the transportation stress while the TS2 goats were still under stress. As for the lairage duration, it was observed that the TS2L3 goats showed lower EEG activities than the values obtained after two-hour transportation, while lower EEG activities were found from the TS6L6 goats after six-hour transportation. Therefore, it can be concluded that three-hour lairage was adequate to lower the impact of two hours transportation stress, whereas six-hour lairage was required to reduce the impact of six hours transportation stress. Finally, it was also found that the TS6L3, TS6L6, and TS6L12 groups took a long time to die after slaughter than the TS2L3, TS2L6, and TS2L12 goats based on the time their EEG activity reached isoelectric.